Experience in the use of focused lung ultrasound in the intensive care practice - D. V. Korsunsky; T. G. Utina; O. N. Dzhioeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Surgical interventions, accompanied by a subclavian vein cannulation, are associated with the risk of pneumothorax. Timely detection of this condition reduces the risk of secondary complications. An effective and promising method for the early detection of pneumothorax is lung ultrasound.Aim. To evaluate the routine bedside use of focused lung ultrasound in the early postoperative period in patients after surgical interventions accompanied by subclavian vein cannulation.Material and methods. This retrospective analysis of 304 case records of patients after surgical interventions accompanied by subclavian vein cannulation was carried out. Patients underwent lung auscultation, lung ultrasound according to the Bedside Lung Ultrasound in Emergency (BLUE) protocol 1 and 6 hours after surgery, or unscheduled with a saturation decrease <90%, the appearance of shortness of breath and/or chest pain. When pneumothorax signs were detected, patients underwent an emergency chest x-ray, and an elective x-ray was performed 1 day after the intervention.Results. 304 case records were analyzed, lung ultrasound was performed in 187 (61,5%) men and 117 (38,5%) women. In 8 (2,63%) patients, 1 hour after surgery, an A-profile without lung sliding was detected. In 3 (0,99%) patients, auscultatory breathing weakening was noted, complaints of discomfort and pain during inspiration were noted by 5 (1,64%) patients. In all 8 patients, the diagnosis was confirmed by x-ray. In 5 (1,64%) patients, a mild pneumothorax was detected, which did not require drainage, while 3 patients underwent pleural drainage.Conclusion. Focused lung ultrasound using the BLUE protocol significantly improves the safety profile of patients after subclavian vein puncture, providing high levels of sensitivity and specificity in detecting pneumothorax.